Perbadingan Indeks Maqashid Syariah pada Kinerja Perbankan Syariah di Asia dan Eropa - Maisa Frita Winesa; Mochamad Edman Syarief; Setiawan Setiawan (Journal of Applied Islamic Economics and Finance, 2021)
Performance evaluations in Islamic banking generally use traditional measurement tools. In fact, evaluating the performance of the Islamic banking industry cannot be the same as using traditional banking assessment tools, because Islamic banking and traditional banking have different goals and perspectives. This study aims to analyze the performance of the Islamic banking industry in Indonesia, Saudi Arabia, the United Kingdom and Turkey from 2016 to 2019 based on the concept of the Sharia law maqshid index, and to find out whether there is a difference in the value of the Sharia law maqshid index in Indonesia, Saudi Arabia and the United Kingdom And Turkey in 2016-2019. This research uses data from the financial statements and annual reports of each Islamic bank. This study is a quantitative study using descriptive research methods. Each country (Indonesia, Saudi Arabia, the United Kingdom, and Turkey) has as many as 3 Islamic bank samples, so the total sample of Islamic banks is 12 Islamic banks. The total observations are 48 observations over a period of 4 (four) years (2016-2019). The Kolmogorov-Smirnov test was used to test the normality of the data and to test the hypothesis using the Analysis of Variance (ANOVA). The results of this study indicate that the maqashid index value, the first sharia goal is individual education, the second goal is the establishment of justice, and the third sharia goal is the public interest in Islamic banking in Indonesia and Islamic banking in Saudi Arabia, England and Turkey does not show a significant difference.